«Gute Burschen, deutsche Burschen». Männlichkeit und Schuld in Daniel Kehlmanns «Lichtspiel» - Lukas Krönert (Studia austriaca)
Daniel Kehlmann’s novel Lichtspiel [Play of Light] reflects on the (individual) guilt of Germans in the context of the NS period, as is exemplified in the character of Jakob. He undergoes a radical change, transforming from an open-minded child to a model Nazi. Upon entering the German Reich, he is confronted with new role expectations: Non-compliance with the norms of soldierly masculinity is sanctioned. This essay examines the relations between those norms of masculinity as narrated in Lichtspiel (published in English as The Director) and the reflections of guilt in this context.